Triptolide inhibits the proliferation of cells from lymphocytic leukemic cell lines in association with downregulation of NF-κB activity and miR-16-1* - Meng Hai-tao; Zhu Li; Ni Wan-mao; You Liang-shun; Jin Jie; Qian Wen-bin (Acta Pharmacologica Sinica, 2016)
Aim: To examine the effects of triptolide (TPL) on T-cell leukemia cells and identify their underlying mechanisms. Methods: The cytotoxicity of TPL was assessed by MTT assay. Cell apoptosis was determined using annexin V and DAPI staining and analyzed by flow cytometry or fluorescence microscopy. The activation of caspase pathways and the expression of nuclear factor κB (NF-κB) p65 were examined by Western blotting. Differences in microRNA (miRNA) expression in Molt-4 and Jurkat cells before and after TPL treatment were identified using microarrays and real-time RT-PCR, respectively. Results: TPL 20–160 nmol/L treatment potently inhibited cell growth and induced apoptosis in T-cell lymphocytic leukemia cell lines. Molt-4 and Jurkat cells, however, were more sensitive to TPL than L428 and Raji cells. After 24 h of treatment, bortezomib abrogated the growth of Molt-4 and Jurkat cells with an IC50 of 15.25 and 24.68 nmol/L, respectively. Using Molt-4 cells, we demonstrated that treatment 20–80 nmol/L inhibited the translocation of NF-κB p65 from the cytoplasm to the nucleus and that phosphorylated NF-κB p65 in nuclear extracts was down-regulated in a dose-dependent manner. Similar results were also seen in Jurkat cells but not in L428 cells, as these cells are resistant to TPL and bortezomib (a NF-κB inhibitor). Twenty-three miRNAs were differentially expressed after TPL treatment. Functional analysis revealed that TPL treatment could inhibit expression of miR-16-1* and that transfection of miR-16-1* led to significantly decreased apoptosis induced by TPL. Conclusion: Our in vitro studies suggest that TPL might be an effective therapeutic agent for treatment of T-cell lymphocytic leukemia and that its cytotoxic effects could be associated with inhibition of NF-κB and down-regulation of miR-16-1*.